PEMBERDAYAAN UMKM MELALUI SOSIALISASI DAN PELATIHAN KERAJINAN TANGAN BOUQUET (HANDYCRAFT) KEPADA PEMUDA-PEMUDI DI LINK BERIGIL - Dewi safitri; Nazlah Azzahra; Nisrina Alya Salsabila; Maesaroh Maesaroh; Ayu Safitri; M. Farhan Hidayatullah; Khoirunnisa Khoirunnisa; Lailatul Zannah; Rian Firmansyah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Micro, Small, and Medium Enterprises (MSME) empowerment activities play a strategic role in enhancing the economic independence of communities, particularly among the youth at the local level. This study aims to describe the process and outcomes of MSME empowerment through the dissemination and training of handmade bouquet craftsmanship to young people in the Berigil neighborhood, Suralaya Village. The research method employed was participatory observation and documentation, as the researcher was directly involved in the training activities. The results of the activities demonstrated an increase in the knowledge and skills of young people in producing creative products, the formation of small business groups, and the growth of entrepreneurial spirit and awareness of the importance of product innovation for market competitiveness. Thus, the socialization and training program for handmade bouquets has proven effective as a sustainable MSME empowerment strategy at the village level.